Changes in precipitation from 1958 to 2012 in arid and semiarid regions of northern China. (2017) - Li, Jinchang; Zhao, Yanfang; Fan, Xiaohui
We used a precipitation dataset from 1958 to 2012 in arid and semiarid regions of northern China, to look for monotonic trends and 'steps' (abrupt changes) in the trends for annual and seasonal precipitation. We found that annual precipitation during the study period had decreased in semiarid regions, mainly caused by decreasing precipitation during the rainy season, versus increases in eastern arid and western arid regions, mainly caused by increasing precipitation in the pre-rainy season and winter. An abrupt increase in the pre-rainy season precipitation occurred in the semiarid, eastern arid, and western arid regions in the early to mid-1980s, which was consistent with the period when rehabilitation of aeolian desertified land began in these regions. Therefore, the change in pre-rainy season precipitation may have been the key factor responsible for changes in aeolian desertification in arid and semiarid regions of northern China.